Response of mustard to boron fertilization (Bangladesh Journal of Agricultural Research, 2013)
A field experiment was carried out in non-Calcareous Floodplain Soil of Spices Research Sub-Station, Lalmonirhat under AEZ 2 during the rabi season of 2007- 2008 and 2008-09. The objectives were to evaluate the effect of boron on the yield of mustard and to screen out the suitable variety tested against different boron levels for maximizing yield. Three varieties of mustard viz., BARI Sharisha-11, 13, and 14 and 5 levels of boron (0, 0.5, 1.0, 1.5 and 2.0 kg/ha) along with a blanket dose of N120 P35 K65 S20 Zn3.0 kg/ha were used in the study. Results revealed that BARI Sharisha-11 performed better with 1.5 kg B/ha which produced 1.82 t/ha seed. However, from regression analysis, a positive but quadratic relationship was observed between seed yield and boron levels. The optimum dose of boron was appeared to be 1.7 and 1.6 kg B/ha for Lalmonirhat during 2007-08 and 2008-09, respectively. DOI: http://dx.doi.org/10.3329/bjar.v37i4.14392 Bangladesh J. Agril. Res. 37(4): 677-682, December 2012